AKSES KE SARANA SANITASI DASAR SEBAGAI FAKTOR RISIKO KEJADIAN STUNTING PADA BALITA USIA 6-59 BULAN - Hasan, Amrul; Kadarusman, Haris (Jurnal Kesehatan, 2019)
Stunting is a condition of failure to thrive in children under five (infants under five years old) due to chronic malnutrition so children are too short for their age. Toddlers are short (stunted) and very short (severely stunted) are toddlers with body length (PB/U) or height (TB/U) according to their age compared to WHO-2010 standard. The research objective was to analyze the relationship between Access to Basic Sanitation Facilities and Stunting Events in children aged 6-59 months in East Lampung Regency. The study using a case-control design with a population was all children aged 6 to 59 months in nine stunting locus villages in the Regency East Lampung in 2018. Cases are 200 stunting children, controls are 200 children in normal status. Cases were taken from nine villages which were designated as stunting loci, while controls were normal toddlers who were in one integrated healthcare center with cases. Data collection by interview and measurement and observation. Univariate, bivariate data analysis, and multivariate (multiple logistic regression test). The results of the multivariate analysis found two variables related to the incidence of stunting, namely access to healthy latrines OR 5,99 (95%CI:2,98-9,23), Access to clean water sources OR=5,99 (95% CI:3,31-10,83), after being controlled by variable history of infectious diseases, history of MPASI administration and history of growth monitoring. Access to healthy latrines and access to clean water sources that meet health requirements is a risk factor for stunting after adjusting for the variable history of infectious disease, history of MPASI administration, history of growth monitoring.